Answer:
a=6x
Step-by-step explanation:
Given the logarithmic equation:
![\log _(4^x)2^a=3](https://img.qammunity.org/2023/formulas/mathematics/college/z7vjpq8jtxddwmmxxes3jg933z8rlus07e.png)
We appy the change of base rule:
![\begin{gathered} \log _ab=(\log b)/(\log a) \\ \implies\log _(4^x)2^a=(\log2^a)/(\log4^x)=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yjce3igu21xbuf25rxp2a6n1beox3jj7lx.png)
Next, rewrite 4 as a power of 2.
![\begin{gathered} (\log2^a)/(\log4^x)=3 \\ \implies(\log 2^a)/(\log 2^(2x))=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ffwo8o0k737zospq1loydht6vid2oxb53v.png)
Take the index of the numbers as the product by the index law.
![(a\log 2)/(2x\log 2)=3](https://img.qammunity.org/2023/formulas/mathematics/college/7svpp9dh2cxvi8p7phgpj56tuglh62y56q.png)
Cancel out log 2 in the numerator and denominator
![\implies(a)/(2x)=3](https://img.qammunity.org/2023/formulas/mathematics/college/axpup9hj1evea035d7919fs316wdx9iz5s.png)
Finally, cross multiply to express "a" in terms of x.
![\begin{gathered} a=3*2x \\ a=6x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vgy0jkkf55fzzxksyuj4g8161lzyhm178g.png)